Radial Basis Function approximations for partial differential equations - BRIK, OSEMA; GAGUI, Bachir: Supervisor (Mohamed Boudiaf University of M'sila, 2024)
In this work, we introduce the radial basis functions and their types, and we applied this technique to solve the Laplace, Poisson and telegraph equations, these solutions are approximates solutions.
Keywords: Radial Basis; Function approximation; partial differential equations